Analysis Of Parental Involvement In Supporting Quality Early Childhood Education : A Qualitative Case Study - Libri Rizka Puri Windarta; Maulidya Ulfah; Firda Fauziah (Jurnal Pendidikan Raudhatul Athfal, 2025)
This study aims to describe the planning, implementation, as well as the supporting and inhibiting factors of parental involvement in supporting quality early childhood education at TKIT Sholahuddin Al Ayyubi, Sumedang. This research adopts a descriptive qualitative approach, which seeks to describe, explain, and answer questions related to ongoing phenomena and events. Through this approach, the study provides an in-depth understanding of the observed situation. The results showed that parental involvement at TKIT Sholahuddin Al Ayyubi, Sumedang in supporting quality ECE is carried out through three stages: planning, implementation, and evaluation of supporting and inhibiting factors. At the planning stage, parental involvement is reflected in school committee meetings, school program development, and collaboration with external institutions such as health centers. However, some parents are still not actively involved in the planning process. At the implementation stage, parental involvement is reflected in activities such as parenting sessions, parent classes, supplementary feeding programs, early detection of growth and development, clean and healthy living behavior programs, and Collection of National Identification Numbers for the Basic Education Data System. The school also supports healthy habits by providing sanitation and clean water facilities. The supporting factors for parental involvement include effective communication, mutual commitment, and adequate facilities, which help strengthen cooperation between parents and the school. Inhibiting factors include limited time, parents' busy work schedules, and a lack of understanding about the importance of parental roles in early childhood education. Suggestions for institutions, teachers, and parents include enhancing collaboration through effective communication, training programs, and encouraging active participation in children's education. This also involves strengthening the role of parents both at home and at school in order to help achieve high-quality early childhood education. Keywords: parental involvement, quality of early childhood education, young children.